NEPHROPROTECTIVE ACTIVITY OF ASPARAGUS RACEMOSUS AGAINST CISPLATIN-INDUCED NEPHROTOXICITY AND RENAL DYSFUNCTION IN EXPERIMENTAL RATS - Av, Yadav; Cd, Upasani (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The current study was designed to evaluate the protective effect of standardized hydroalcoholic extract of Asparagus racemosus (AR) against cisplatin (CP)-induced nephrotoxicity in Wistar rats. Methods: AR extract was administered orally at three dose levels (100, 200, and 400 mg/kg). Vitamin E (250 mg/kg) was used as a standard nephroprotective agent. The kidney function test (estimation of serum creatinine, albumin, and blood urea nitrogen [BUN]), oxidative stress study (estimation of superoxide dismutase and malondialdehyde [MDA] activity), and histological examination of kidneys were conducted. Results: The efficacy of AR was compared with CP-treated group. Serum creatinine and BUN were significantly (p<0.001) elevated in CP-treated group compared to control group. Hydroalcoholic extract of AR (100, 200, and 400 mg/kg) and Vitamin E (250 mg/kg) significantly (p<0.001) decreased the serum creatinine and BUN levels. CP exhibited significant (p<0.001) decrease in albumin when compared to control. Significant (p<0.001) increase in the serum albumin level was found in extract-treated group compared to CP group. Significant (p<0.001) decrease in activity of superoxide dismutase (SOD) was observed in the CP group as compared to control. AR (100 and 200 mg/kg) significantly (p<0.01) increased SOD levels. AR (400 mg/kg) significantly (p<0.001) increased SOD levels. AR (100, 200, and 400 mg/kg) significantly (p<0.001) decreased MDA levels as compared to CP group. Histopathological examination of the kidneys showed that AR markedly ameliorated CP-induced renal tubular necrosis. Extract was found effective at all doses, although high dose (400 mg/kg) was found to be more effective and comparable with standard group (Vitamin E 250 mg/kg). Conclusion: The present investigation revealed that AR resulted in dose-dependent attenuation of CP-induced renal damage in rats.